Viabilidade técnica e econômica do manejo florestal sustentável em uma área sob concessão na Amazônia Oriental - Rodrigues, Nívea Maria Mafra (2021)
National Forests (Flonas) are conservation units (UC) considered to be of sustainable use, therefore, multiple use of forest resources through forest concessions is allowed. Techniques for sustainable forest management are used in the concessions, and good exploration planning is essential. For a good planning of activities, it is necessary to carry out studies involving the technical and economic analysis of forest exploration. The study was divided into two chapters, the first with the objective of structuring and evaluating forest exploration activities, through the study of times, in a Forest Management Unit (UMF). The second chapter aims to assess the economic viability of the forest concession in an UMF. The study of the two chapters was carried out in Flona de Saracá-Taquera, located in the municipalities of Faro, Oriximiná and Terra Santa, UMF-II and UMF-1A, Annual Production Unit 3 and 6 (UPA-3 and UPA-6). The cost and revenue information was obtained through interviews with the responsible technical team, purchase and production control files, and information collected in the field. In chapter one, log cutting and skidding cycles were monitored and timed, and later, standard time, normal time and breaks were estimated for each stage of the cycle and for the operational cycle. In addition, efficiency and operational productivity were estimated, as well as a regression analysis of productivity as a function of skidding distance. The fit of the model was evaluated based on the coefficient of determination (R²) and the relative standard error (Syx%). Based on the results, it was observed that the sampling error obtained for the cutting cycle was 14.03% and 5.03% for the skidding cycle. The variation coefficients were high for both cycles, indicating irregular times. The operational efficiency of the cutting and skidding cycles were 96.87% and 96.55%, respectively. The skidding distance had a significant influence (p <0.05) on the average productivity, explaining 70% of the variation in productivity. In chapter two, a cash flow was drawn up including all forestry activities carried out at UMF-II and production revenues considering a 30-year cut cycle. The methods used as economic indicators were the Net Present Value (NPV), the Internal Rate of Return (IRR) and the Revenue / Cost Ratio (R / C). The most representative costs were with transport and dragging of logs, corresponding to 39.81% of the total cost. Positive NPVs were obtained for the base scenario and for the 10% reduction in the price of wood paid to the Brazilian Forest Service. Considering the changes in the value of wood in the market, the base scenario and with an additional 10% were economically viable, however, the scenario of a 10% reduction in value presented negative NPVs.